THE CONCEPT OF THE WOLF IN KARAKALPAK LINGUOCULTURE (TAMADDUN NURI JURNALI, 2025)
The article provides a linguocultural analysis of wolf zoonym describing the meaning of man in the Karakalpak language.It is associated with the identity of wolf and witch, euphemism and religious beliefs of the people. It is scientifically proved that zoonimic euphemisms are connected with the national mentality and customs of the Karakalpak people. In the group of zoonimic euphemisms totemistic attitudes of the people are inherited and have reached the limits by the present time.